PENGARUH UKURAN PERUSAHAAN, KINERJA KEUANGAN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KEBIJAKAN DIVIDEN - Komang Krishna Yogantara; Gde Herry Sugiarto Asana; Made Hedy Wartana (Journal of Applied Management and Accounting Science, 2022)
The dividend policy of food and beverage companies still tends to fluctuate. Some companies don't even pay dividends for five years in a row. This means that companies in the food and beverage sector each year have not been consistent in making dividend policies. The purpose of this study was to determine the effect of firm size, financial performance and institutional ownership on dividend policy in food and beverage companies on the IDX. The research was conducted with a quantitative approach, with a porpose sampling technique. The companies that were sampled were 29 food and beverage companies with a research period of 2018-2020. The data analysis technique was carried out by multiple linear regression analysis with the help of the SPSS program. Hypothesis testing was carried out using the t test, F test and R2 test. The results showed that firm size had a significant effect on dividend policy, financial performance had no significant effect on dividend policy, institutional ownership had no significant effect on dividend policy and firm size, financial performance and institutional ownership had a significant effect on dividend policy in food and beverage companies on the IDX. period 2018-2020.